(3eLed GddZIs - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s ((3GHh YHO Gddg Hf fGei Hf eSde Gdfjdi s)
(3ChdgG (B:s
(3Chd GdehLhO efg GKfGA MQa GdUGO bhdg hUMMg HGdShW VQHg , hGdUMGM Gdci hGdUeGM GdfJf hGdUeGLI GdecGf GdNTf s
(3BNQgG (B:s
(3dGf GdjGA GfeG jYJHQ HgG ai gPjf GdHGHjf GdMQa GdPi HYOgG hbO eVi cdg ai CHhGH GdcJGH hgPG BNQ eLed GddZI Je GdcJGH hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B193 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B40s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs